Multidimensional analysis of register variation in English translations of Shijing - Baohu Li; Guangwei Li (PLoS ONE, 2025)
This study employs Multidimensional Analysis (MDA) to compare the register of Arthur Waley’s and Ezra Pound’s translations of Shijing, and further explores the factors contributing to their differences. The key findings are as follows: (1) Waley’s translation corresponds to the “involved persuasion” register, characterized by high interactivity and extensive informational elaboration. In contrast, Pound’s translation aligns with the “general narrative exposition” register, emphasizing informativeness and narrativity; (2) The interactivity in Waley’s translation is primarily driven using analytic negation, first-person pronouns, and modal verbs, while the elaboration is attributed to the frequent use of demonstrative pronouns. In contrast, Pound’s translation exhibits strong informativeness due to the frequent use of nouns and prepositional phrases, while its narrativity is shaped by synthetic negation and public verbs; (3) Waley’s approach prioritizes an accurate reflection of ancient Chinese society and the preservation of cultural heterogeneity. In contrast, Pound’s translation focuses on didacticism, emotional energy, and precision. The differences in the translators’ ideologies and poetic philosophies are identified as the primary factors accounting for the register variations in their translations.